Recent developments in alumina supported hydrodesulfurization catalysts for the production of sulfur-free refinery products: A technical review. Issue 1 (2nd January 2022) - Shafiq, Iqrash; Shafique, Sumeer; Akhter, Parveen; Yang, Wenshu; Hussain, Murid
ABSTRACT: Hydrodesulfurization is a valuable cornerstone in the modern refineries, aiming to reduce sulfur-containing compounds to produce cleaner end-products, by using heterogeneous metal catalysts at elevated temperatures and hydrogen pressures. The removal of refractory sulfur is a great challenge in commercial HDS of diesel fuels. This prospective review briefs synthesis factors influencing the performance of an efficient catalyst aiming for the removal of sulfur from transportation fuels, more specifically in the diesel fuels. The first part of the paper presents concepts, principles, advantages, and challenges of existing HDS processes. Special consideration is remunerated in the second part, in which the recent advances governed for the development of a new generation of catalysts, that are being developed for ultra-low sulfur fuels are discussed comprehensively. These developmental studies are critically reviewed to summarize advanced strategies for the catalyst synthesis and to formulate an adequate catalyst activity to accomplish forthcoming sulfur regulations on transportation fuels. Graphical Abstract: uf0001